Coverage Root after Removing Peripheral Ossifying Fibroma: 5-Year Follow-Up Case Report - Paulo S. G. Henriques; Luciana S. Okajima; Marcelo P. Nunes; Victor A. M. Montalli (Case Reports in Dentistry)
When lesions in soft tissue reach the gingival margin, they can produce aesthetic defects during its permanence and after its removal. Periodontal plastic surgery allows the correction of the gingival contour using different techniques. This paper is a case report of a peripheral ossifying fibroma removal in the interproximal area of teeth 21 and 22 in addition to root coverage of the affected area through two surgical phases: keratinized gingival tissue augmentation surgery with free gingival graft concurrent with removal of the lesion and, in a second stage, root coverage by performing coronally advanced flap technique with a follow-up of five years. The initial results achieved, which were root coverage of 100% after 6 months, promoted an adequate gingival contour and prevented the development of a mucogingival defect or a root exposure with its functional and aesthetic consequences. After five years, the results showed long term success of the techniques, where the margin remained stable with complete root coverage and tissues were stable and harmonic in color.